Does increased interdisciplinary contact among hard and social scientists help or hinder interdisciplinary research? - Urbanska, Karolina (PLoS One, 2019)
Scientists across disciplines must often work together to address pressing global issues facing our societies. For interdisciplinary projects to flourish, scientists must recognise the potential contribution of other disciplines in answering key research questions. Recent research suggested that social sciences may be appreciated less than hard sciences overall. Building on the extensive evidence of ingroup bias and ethnocentrism in intergroup relations, however, one could also expect scientists, especially those belonging to high status disciplines, to play down the contributions of other disciplines to important research questions. The focus of the present research was to investigate how hard and social scientists perceive one another and the impact of interdisciplinary collaborations on these perceptions. We surveyed 280 scientists at Wave 1 and with 129 of them followed up at Wave 2 to establish how ongoing interdisciplinary collaborations underpinned perceptions of other disciplines. Based on Wave 1 data, scientists who report having interdisciplinary experiences more frequently are also more likely to recognise the intellectual contribution of other disciplines and perceive more commonalities with them. However, in line with the intergroup bias literature, group membership in the more prestigious hard sciences is related to a stronger tendency to downplay the intellectual contribution of social science disciplines compared to other hard science disciplines. This bias was not present among social scientists who produced very similar evaluation of contribution of hard and social science disciplines. Finally, using both waves of the survey, the social network comparison of discipline pairs shows that asymmetries in the evaluation of other disciplines are only present among discipline pairs that do not have any experience of collaborating with one another. These results point to the need for policies that incentivise new collaborations between hard and social scientists and foster interdisciplinary contact.